Influence of aging time to achieve tensile build direction heat treated T74 forging properties in lubricant free AFSD AA7050 - I. Liu; J. Hoarston; N. Zhu; A. Birt; N. Palya; B.J. Phillips; D.Z. Avery; P.G. Allison; J.B. Jordon (Additive Manufacturing Letters, 2025)
The need for long-lead time aluminum alloy casting and forging replacements requires innovative solutions such as Additive Friction Stir Deposition (AFSD), a solid-state additive manufacturing technique that uses frictional heat and severe plastic deformation to create metallurgical bonds through layer-by-layer deposition. While AFSD has demonstrated isotropic mechanical properties in the as-deposited condition, post-deposition heat treatment (PDHT) of precipitation hardened aluminum alloys processed by AFSD has led to poor ductility, particularly in the build direction. In this feasibility study, a lubricant-free twin rod AFSD (TR-AFSD) approach printed a 100 millimeter tall AA7050 build. Mechanical properties in the build direction were determined for a range of artificial aging times. Experimental results showed that a one hour aging time following a 24-hour solution treatment produced tensile yield, ultimate tensile strength, and strain to failure results of 360 ± 5.5 MPa, 463 ± 10.3 MPa, and 7.55 ± 2.00 %, respectively. Our feasibility study shows that forging-like tensile properties can be achieved in the build direction from TR-AFSD prints using a featureless tool coupled with a temperature control lubricant-free round feedstock approach and a custom PDHT schedule.